The Meaning of Hebrew Term מַחֲּמַדִּ֑ים (Mohamadim) In Song of Songs 5:16: An Exegetical Study - Blasius Abin; Suryanica Aristas Pasuhuk (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Hebrew term מַחֲּמַדִּ֑ים (mohamadim) in Song 5:16 phonetically has proximity with the name of Muhammad. On that basis, some Muslim writers and preachers have a conviction that the text contains a predictive prophecy about Muhammad. This study aimed to indicate what exactly the text says and whether the text inherently comprises a prophecy about Muhammad. Through the historical-grammatical method, this study specifically discusses of literal context, semantic, genre, and theology of the mentioned text. The following are the conclusions of the study: First, Song 5:16 is an account of God’s love that explicated by the author through poetic form. This character of God is materialized at the level of a love relationship between the bride and groom. Second, the presupposition that the term mohamadim refers to the prophet Muhammad is flawed. Semantically, the Hebrew term mohamadim comes from the root mahmad, meaning “desirable, sweet.” Conversely, in Arabic, the name Muhammad comes from the root hammd, which means “to praise” or” praiseworthy.” Hence, the Hebrew term mohamadim has no semantic parallel with Muhammad. Third, the author did not mention locus such as Mecca or Medina where Muhammad or Islam emerged. The city of Jerusalem, where God built the temple as the worship center of Israel, is the locus mentioned by the author. Thus, text Song 5:16 and the entire corpus of the Scripture, whether expressed through poetry or narrative depicted God’s love for human beings and vice versa.